NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM KISAH-KISAH YANG TERKANDUNG AYAT ALQURAN - NUGROHO, IRHAM (Jurnal Pendidikan Islam, 2017)
Allah SWT told us  that in the story of the assabiquunal awwalun  there were lessons learned for the thinking people, which is able to contemplate the stories, finding her wisdom and advice, as well as digging of the stories are life lessons and instructions. Story method is one of God ways in educating and teaching people. This is in line with the conditions that psychologically human loves stories. Hopefully using story methods, we can deliver educational messageseffectively without anyone feeling patronized. In Qur'an, Allah tells examples (uswah hasanah)and lessons (ibrah)for all of us through the stories of the Prophet, figures, and the earlier people.  By referring to the stories found in Qur'an, we can conclude that the Qur'an is a way of life that explains the life of past, present and future. The Qur?an also teach us about the educational value of monotheism, intellectual, moral / moral, sexual, spiritual, democracy.